Teucrium tomentosum B.Heyne ex Benth. (Lamiaceae), an unnoticed later homonym for almost two centuries - Kumar, Venkatachalam Sampath; Chakrabarty, Tapas (Phytotaxa, 2016)
Teucrium tomentosum Heyne ex Bentham (1830: 58) was described based on the specimens presumably collected by Benjamin Heyne from peninsular India. This name was used for almost two centuries in Indian and Ceylonese floras (e.g. Hooker 1885, Trimen 1895, Willis 1911, Gamble 1924, Mukerjee 1940, Cramer 1981, Rani & Mathew 1983, Sharma et al. 1984, Srinivasan 1987). However, the Bentham’s name is an illegitimate later homonym of T. tomentosum Lamarck (1779: 407) and T. tomentosum Moench (1794: 382). A new name is proposed here for this later homonym.